Analysis of patients with prostate cancer care at a reference hospital in the state of Tocantins, suitable for brachytherapy (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Observation and identification of predictive factors for results and morbidity are essential in the ideal selection of patients who can use brachytherapy as a treatment modality for prostate cancer. Thus, the objective of this research is to analyze the population of patients with prostate cancer treated at the General Public Hospital of Palmas in 2015, in the state of Tocantins. The method used was quantitative, with the characteristics of a retrospective, transversal and descriptive analysis. Held in the largest state health unit, the General Public Hospital of Palmas that, despite its large dimensions, lives with the main problems of the Unified Health System, such as overcrowding and shortages. It was found that most of the patients seen corresponded to the age of 70 to 79 years, making 45%, followed by patients aged between 60 and 69 years, with 33%. Most of the individuals attended were from the state of Tocantins, but some lived in an adjacent city in the state of Pará. Data related to the Gleason score showed that there was a predominance of levels 6 and 7 indicating intermediate grade tumors, considering that the most of the observed population was older. It was concluded that the analyzed patients had a predominant staging of CaP II and III, thus most of the individuals, 23 of the 35 analyzed, were not able to undergo brachytherapy due to the high degree of disease staging.